PERTANGGUNGJAWABAN AHLI WARIS ATAS KEWAJIBAN PEWARIS : ANALISIS PEWARIS DAN IMPLEMENTASINYA - Rayi Kharisma Rajib; Moh Rafli Dela Umala; Muhammad Fathurrahman (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the responsibility of heirs for the obligations of the testator from a civil law perspective and examine its implementation in practice in Indonesia. This study uses a normative legal research method with a statutory and conceptual approach. The legal material collection technique is carried out through literature studies, while the analysis is carried out qualitatively with descriptive-analytical methods. The results of the study indicate that the responsibility of heirs for the testator's debts is a consequence of the transfer of rights and obligations based on the principle of saisine, but is not absolute because it depends on the legal attitude of the heirs, while beneficiare acceptance limits responsibility only to the value of the inheritance, and rejection of inheritance frees the heirs from all obligations of the testator. In practice, the implementation of these provisions still faces various problems, such as the unclear boundary between pure acceptance and tacit acceptance, low public understanding of law, and the complexity of beneficiare acceptance procedures. Therefore, clear norms and implementation guidelines are needed to ensure legal certainty and create a balance between the protection of heirs and the interests of creditors.